2014
DOI: 10.3233/jpd-140399
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Walking from the Perspective of People with Parkinson's Disease

Abstract: Background: Parkinson's disease (PD) is associated with progressive mobility and walking difficulties. Although these aspects have been found to be central from a patient perspective, the perceived significance of walking is less well understood. Objective: To explore the significance of walking as perceived and experienced by individuals with PD. Methods: Eleven persons with PD (seven men; median age, 71 years; median PD duration, 7 years) participated. Data were collected through semi-structured interviews, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…[27][28][29][30][31] The articles in the present review suggested that certain dimensions such as life engagement, purpose in life, self-acceptance, environmental mastery, and personal growth are associated with less disability (both motor and non-motor symptoms) in PD. [44][45][46][47] Thus, it appears that the protective role of PWB in adjusting to PD is confirmed, but it still needs further investigations, with standardized psychometric tools. Studies included in this review assessed PWB mainly with open-ended interviews.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[27][28][29][30][31] The articles in the present review suggested that certain dimensions such as life engagement, purpose in life, self-acceptance, environmental mastery, and personal growth are associated with less disability (both motor and non-motor symptoms) in PD. [44][45][46][47] Thus, it appears that the protective role of PWB in adjusting to PD is confirmed, but it still needs further investigations, with standardized psychometric tools. Studies included in this review assessed PWB mainly with open-ended interviews.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining studies mainly considered only psychological indicators, such as depression, anxiety, coping strategies, or other indicators of quality of life. 38,40,41,[43][44][45]47 Bearing all these limitations in mind, an important common finding that emerged from the review of these articles concerns the preservation of motor skills. It is fundamental for maintaining LS, well-being, and favoring social contribution of patients with PD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations